2019
DOI: 10.1039/c9ta01953g
|View full text |Cite
|
Sign up to set email alerts
|

Dual-nitrogen-source engineered Fe–Nx moieties as a booster for oxygen electroreduction

Abstract: The improved ORR performance is attributed to the rich density of the Fe–Nx moieties derived from regulated coordination structures using dual-nitrogen-sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…The chemical states of N1s were studied in detail via the high‐resolution N 1s spectrum (Figure 3e). The spectrum could be fitted with three different N species, which correspond to pyridinic‐N (398.1 eV), pyrrolic‐N (400.0 eV), and graphitic‐N (401.6 eV),55,56 respectively. Considering the size difference between N and C atoms, the introduction of N may cause the structure change of carbon materials, such as more structural defects 57.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical states of N1s were studied in detail via the high‐resolution N 1s spectrum (Figure 3e). The spectrum could be fitted with three different N species, which correspond to pyridinic‐N (398.1 eV), pyrrolic‐N (400.0 eV), and graphitic‐N (401.6 eV),55,56 respectively. Considering the size difference between N and C atoms, the introduction of N may cause the structure change of carbon materials, such as more structural defects 57.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] These devices use the oxygen reduction reaction (ORR), at the cathode of fuel cells and during the discharge process of metal-air batteries. [9][10][11][12][13][14][15] The performance of fuel cells and metal-air batteries is significantly limited by the sluggish ORR kinetics. [16][17][18] Therefore, tremendous efforts in both academia and industry have been made on developing advanced electrocatalysts and/or electrode materials for the cathode of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] The cutting-edge Pt ORR catalyst can achieve higher than 10 A mg Pt −1 at 0.9 V in mass activity by rotating disk electrode evaluation 28 ; even in membrane electrode assemblies, the PtCo catalyst can reach over 1.5 A mg Pt −1 at 0.9 V. 29 However, the biggest challenge for PGM-based ORR catalyst is the scarce resource of PGM and its high cost, so that intensive efforts have been made on developing advanced PGM-free ORR catalysts in the last decades. [30][31][32][33][34][35][36][37][38] Two of most representative types of PGM-free ORR catalysts, the heteroatom (eg, N) doped carbon [39][40][41][42] and the transition metal (eg, Fe) coordinated with N in carbon matrix 11,[43][44][45] have been well accepted as the promising candidates to replace PGM-based materials. In both cases, carbon is the major component 46 ; even for the PGM-based ORR catalysts, carbon support is an important investigation topic.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34,45 ] To improve the nitrogen content in the final catalysts, a dual‐nitrogen‐source method was recently developed using both 1,10‐phenanthroline and urea that was of high nitrogen content and small molecule size. [ 55 ] The dual‐nitrogen‐source precursor was employed to synthesize a high‐performance Fe‐N‐C catalyst where the well‐controlled FeN x moiety was formed. [ 55 ] On the other hand, it has been revealed that the optimal FeN 4 sites derived from ZIF‐derived N‐doped‐carbon and Fe 3+ precursors are attributed to: 1) the transformation from ultrafine FeO x particles to FeN 4 and 2) the improved strength and shortened length of FeN bonds by increasing pyrolysis temperature from the room temperature to 700 °C.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
“…[ 55 ] The dual‐nitrogen‐source precursor was employed to synthesize a high‐performance Fe‐N‐C catalyst where the well‐controlled FeN x moiety was formed. [ 55 ] On the other hand, it has been revealed that the optimal FeN 4 sites derived from ZIF‐derived N‐doped‐carbon and Fe 3+ precursors are attributed to: 1) the transformation from ultrafine FeO x particles to FeN 4 and 2) the improved strength and shortened length of FeN bonds by increasing pyrolysis temperature from the room temperature to 700 °C. [ 56 ] Further increased temperature leads to the loss of nitrogen.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%